Effect of Breed and Fattening System on Fattening Performance, Rumen and Blood Parameters in Akkaraman, Karayaka and Herik Lambs Under Indoor Conditions - Ugurlu, Mustafa; Uysal, Akif; Nacar, Buket; Bolukbas, Bora; Atalar, Furkan; Ay, Deniz; Akdag, Filiz (Ankara University, 2025)
This research was performed to determine comparative effect of concentrate and forage-based diets on fattening performance, rumen and blood serum parameters of Akkaraman, Karayaka and Herik lambs under intensive indoor conditions. In this study forty-five single male lambs, aged 2.5-3 months, were randomly selected from the same flock of each breed. The lambs were divided into two different concentrate/forage ratios (70/30 and 30/70) for each breed. The lambs were fed with concentrated feed and dry alfalfa until they reached 40 kg slaughter weight. In both of diet groups, average daily weight gain (ADWG) and feed conversion rate (FCR) for Akkaraman lambs were better than those of Karayaka and Herik lambs. The rumen pH of the concentrate groups was significantly lower than that of the forage groups for all breeds (P < 0.001). Total volatile fatty acid (TVFA) for Herik lambs was higher than that of Akkaraman and Karayaka lambs in both of diet groups. TVFA and total ammonia nitrogen (NH3-N) concentrations of lambs in the concentrate groups were significantly higher than those of the lambs in the forage groups (P < 0.001). Consequently, the study indicates that fattening performance for Akkaraman lambs was better than that of Karayaka and Herik lambs in both of diet groups, as shown by higher ADWG and better FCR values. The diet was effective (P < 0.001) on all rumen parameters. Also, the present study confirms that blood parameters have normal levels.
Keywords: Blood Parameters; Fattening Performance; Lamb; Rumen Parameters